2022
DOI: 10.1002/jsfa.12328
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal treatment of hemp seeds (Cannabis sativa L.): impact on its dehulling yield, fatty acid profile and nutritional characteristics

Abstract: BACKGROUND: Hemp seeds are highly nutritious and a sustainable source of protein and omega-fatty acids. The outer shell of the seeds restricts its utilization in the food industry. Dehulling of the seeds leads to a lot of processing losses due to high oil content and hard shell of the seed. Therefore, in the present study, hydrothermal treatment of the hemp seeds (Cannabis sativa L.) before dehulling was proposed to reduce the endosperm breakage and improve dehulling yield of seeds.RESULT: The hemp seeds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Removing the hull eliminates or reduces the contents of antinutrients, improves the sensory properties of the dehulled seeds, and enhances their digestibility [ 42 , 43 ]. Previous work [ 27 , 43 , 44 ], and our presented results, have confirmed that dehulling can also be an important technological step in producing hemp seed protein concentrates and isolates, while this step removes big amounts of ballast substances (especially fibre components). At the same time, the proteomic results indicate the importance of hemp seed hulls as a source of a specific protein.…”
Section: Resultssupporting
confidence: 84%
“…Removing the hull eliminates or reduces the contents of antinutrients, improves the sensory properties of the dehulled seeds, and enhances their digestibility [ 42 , 43 ]. Previous work [ 27 , 43 , 44 ], and our presented results, have confirmed that dehulling can also be an important technological step in producing hemp seed protein concentrates and isolates, while this step removes big amounts of ballast substances (especially fibre components). At the same time, the proteomic results indicate the importance of hemp seed hulls as a source of a specific protein.…”
Section: Resultssupporting
confidence: 84%